Forensic Stylistics: Exploring Style and Variations Across Different Writing Positions - Vinny Sharma; Sharda Yadav; Suneet Kumar (Indian Journal of Forensic Medicine and Pathology, 2025)
Background: Handwriting is a complex task as it involves neuromuscular efforts. It is a written language through any mark, drawing, or symbol to convey a meaningful message. Hence, handwriting is a medium of communication, even a single stroke can be a whole message between the communicators. Handwriting is an acquired skill inÁuenced by many factors such as different bodypositions, different writing instruments, writing content, writing techniques (copy, dictated, or after recall), etc. Aim and Objective: This paper presents a study of the style markers and variation across the written sample, when writing is executed by a person in different body positions. Material: To achieve this study, 125 writing samples were collected from 25 participants aged 19-45 years. Each of the participants has written the sample in four different positions after 𿿿lling out the basic questionnaire. The percentage istribution of variations in the handwriting characteristics and style markers associated with it was studied. Result: During the analysis, it has been observed that copying similar content in different body positions results in variations in the general characteristics of the person’s writing, including style pattern and which further draws into the range of variations in the handwriting characteristics and Individual’s stylistic pattern during different writing positions. Conclusion: This study will be helpful for forensic document examiners to lead to more accurate opinions. These observations might justify the examination of writings from different body positions as proof in a court of law when a similar condition of writing is in dispute.